Mortalité d`une cohorte de 514 cyclistes de haut niveau - Morcet, J.; Perrin,M.; Trégaro,M.; Carre, F.; Deugnier,Y. (Science & Sports, 2012)
Aim: The effect of high-level cycling practice on mortality is not known. This study was aimed at assessing mortality and death causes in a cohort consisting of the 514 top male cyclists of the Triomphe Breton from 1960 to 1990. Patients and results: Data were obtained from Inserm and Insee national files, and standardized mortality ratios calculated with reference to the male general population of Brittany. On the 31/12/08, 508 subjects (98.8%) were analysable: 476 were alive after a median follow-up of 31 years and 32 dead (of which 19 from external causes and eight from cancers). This corresponded to an under mortality for every causes with, however, higher mortality rates in youngest than in oldest cyclists. This study has permitted to set up a reference cohort of elite road cyclists and to show a lower mortality of these subjects compared to the general population. Conclusion: The trend towards increasing mortality rates in youngest subjects justifies continuing the follow-up of the cohort.